Desmopressin for treatment of platelet dysfunction and reversal of antiplatelet agents: a systematic review and meta‐analysis of randomized controlled trials. (8th February 2017) - Desborough, M. J. R.; Oakland, K. A.; Landoni, G.; Crivellari, M.; Doree, C.; Estcourt, L. J.; Stanworth, S. J.
Abstract : Essentials The optimal management of patients with platelet dysfunction undergoing surgery is unclear. This meta‐analysis compared perioperative administration of desmopressin to placebo. Desmopressin reduced red cell transfusions, blood loss and risk of re‐operation due to bleeding. There were too few events to determine if there was a change in the risk of thrombotic events. Summary: Background: Platelet dysfunction, including that caused by antiplatelet agents, increases the risk of perioperative bleeding. The optimal management of patients with platelet dysfunction undergoing surgery is unclear. Objectives: To assess whether desmopressin reduces perioperative allogeneic red cell transfusion and bleeding in patients with platelet dysfunction. Patients/Methods: We searched for randomized controlled trials in The Cochrane Central Register of Controlled Trials, MEDLINE, PubMed, Embase, the Transfusion Evidence Library and the ISI Web of Science to 7th July 2016. Data were pooled using mean difference (MD), relative risks or Peto odds ratios (pOR) using a random‐effects model. Results: Ten trials with 596 participants were identified, all in the setting of cardiac surgery. Platelet dysfunction was due to antiplatelet agents in six trials and cardiopulmonary bypass in four trials. Patients treated with desmopressin were transfused with fewer red cells (MD, −0.65 units; 95% Confidence Interval [CI], −1.16 to −0.13 units), lost less blood (MD, −253.93 mL; 95% CI, −408.01 to −99.85 mL) and had a lower risk of re‐operation due to bleeding (pOR, 0.39; 95% CI, 0.18–0.84). The GRADE quality of evidence was very low to moderate, suggesting considerable uncertainty over the results Conclusions: Desmopressin may be a useful agent to reduce bleeding and transfusion requirements for people with platelet dysfunction or with a history of recent antiplatelet drug administration undergoing cardiac surgery.